Purification and characterization of oocyte cytoplasmic tubulin and meiotic spindle tubulin of the surf clam Spisula solidissima (The Rockefeller University Press, 1984)
Assembly-competent tubulin was purified from the cytoplasm of unfertilized and parthogenetically activated oocytes, and from isolated meiotic spindles of the surf clam, Spisula solidissima. At 22 degrees C or 37 degrees C, Spisula tubulin assembled into 48-51-nm macrotubules during the first cycle of polymerization and 25-nm microtubules during the third and subsequent cycles of assembly. Macrotubules were formed from sheets of 26-27 protofilaments helically arranged at a 36 degree angle relative to the long axis of the polymer and were composed of alpha and beta tubulins and several other proteins ranging in molecular weight from 30,000 to 270,000. Third cycle microtubules contained 14-15 protofilaments in cross-section and were composed of greater than 95% alpha and beta tubulins. After three cycles of polymerization at 37 degrees C, unfertilized and activated oocyte tubulin self-assembled into microtubules at a critical concentration (Ccr) of 0.09 mg/ml. At the physiological temperature of 22 degrees C, unfertilized oocyte tubulin assembled into microtubules at a Ccr of 0.36 mg/ml, activated oocyte tubulin assembled at a Ccr of 0.42 mg/ml, and isolated meiotic spindle tubulin assembled at a Ccr of 0.33 mg/ml. The isoelectric points of tubulin from both unfertilized oocytes and isolated meiotic spindles were 5.8 for alpha tubulin and 5.6 for beta tubulin. In addition, one dimensional peptide maps of oocyte and spindle alpha and beta tubulins were very similar, if not identical. These results indicate that unfertilized oocyte tubulin and tubulin isolated from the first meiotic spindle are indistinguishable on the basis of assembly properties, isoelectric focusing, and one dimensional peptide mapping. These results suggest that the transition of tubulin from the quiescent oocyte state to that competent to form spindle microtubules in vivo does not require special modification of tubulin but may involve changes in the availability of microtubule organizing centers or assembly-promoting microtubule-associated proteins.